1987
DOI: 10.1021/bk-1987-0340.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic and Morphological Aspects of Recrystallized Cellulose as a Function of Molecular Weight

Abstract: The polymorphism and morphology of cellulose precipitated from solutions in amine oxide by the slow diffusion of water vapors, was investigated, as functions of the temperature of recrystallization and the degree of polymerization(DP) of the material to be recrystallized. At temperatures around 90°C, low DP cellulose crystallized almost exclusively as cellulose IV II , whereas higher DP material was found in the form of cellulose II. Substantial differences were also found in the morphologies of the various sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Thus, it seems that when allowed to crystallize as ribbons in the mannan II family, a low molecular weight mannan will crystallize in one allomorph, whereas a high molecular weight samples will be able to crystallize in another form. Such dependence of the polymorphism on the molecular weight has already been reported for the occurrence of mannan I and mannan II in mannan-based polysaccharides. , It has also been demonstrated in recrystallized cellulose and for (1→3)-β- d -glucan. , So far however, no satisfactory explanation has been given for such a phenomenon. In light of earlier work 12,13 and the present observations, mannan and the related glucomannans appear to be quite versatile in their crystallization mode.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, it seems that when allowed to crystallize as ribbons in the mannan II family, a low molecular weight mannan will crystallize in one allomorph, whereas a high molecular weight samples will be able to crystallize in another form. Such dependence of the polymorphism on the molecular weight has already been reported for the occurrence of mannan I and mannan II in mannan-based polysaccharides. , It has also been demonstrated in recrystallized cellulose and for (1→3)-β- d -glucan. , So far however, no satisfactory explanation has been given for such a phenomenon. In light of earlier work 12,13 and the present observations, mannan and the related glucomannans appear to be quite versatile in their crystallization mode.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, crystallization held at intermediate temperature conditions yielded hybrid interlinked cellulose II/IVII crystals, while the precipitation of a higher DP cellulose results in distorted shapes and loss of crystal structure 31,32 . Furthermore, a different study concluded that low DP cellulose crystallized almost exclusively as cellulose IVII, whereas higher DP material precipitated as cellulose II 38 . Figure 2 summarizes some of the literature findings regarding the crystallization of LMWC into single crystals of cellulose II and IVII.…”
Section: Structurementioning
confidence: 97%
“…In addition, it contains the first cross-team cooperation with the University of Valladolid and reconciliation of experimental results from that research group during the same period 29 . Furthermore, the results on LMWC precipitation were analyzed in light of the extensive and high-quality corpus of literature from the 1970s and 1980s on cellulose crystallization [31][32][33][34][35][36][37][38] . Finally, significant effort was put in characterizing the LMWC produced by supercritical water treatment and to compare it with microfibrillated nanocellulose produced from MCC by mechanical means 39,40 .…”
Section: Afmmentioning
confidence: 99%
See 1 more Smart Citation